Application of vacuum distillation in refining crude lead. (February 2018) - Zhang, Yongwei; Deng, Juhai; Jiang, Wenlong; Mei, Qingsong; Liu, Dachun
Abstract: This paper introduces a new process for refining crude lead by vacuum distillation. The saturated vapor pressures of lead and impurity elements were calculated, and the removal effect of impurity elements was quantitatively predicted using the vapor-liquid equilibrium diagram. In addition, the low temperature followed by high temperature vacuum distillation method and the high temperature followed by low temperature method were adopted to adjust the order of impurity removal. The refining effect was experimentally studied using these two methods, and the best parameters were determined. The predictions are in close agreement with the experimental results. Based on theoretical and experimental analyses, a new, clean and efficient process for refining crude lead was developed. First, the crude lead was distilled by vacuum distillation at 10 Pa and 1673 K for 30 min, and then, the volatiles and residues were collected. Second, the volatiles were vacuum distilled at 10 Pa and 1273 K for 30 min. The removal rates of Cu, Sn, Ag, Zn, Sb and Bi were 99.73%, 99.72%, 96.23%, 90.78%, 74.80% and 8.82% respectively, and the purity of Pb reached 99.03%. Highlights: A new two-stage vacuum distillation method for refining crude lead was proposed by vacuum distillation theory. The refining of crude lead using Vacuum distillation was predicted based on the Principle of Vapor-Liquid Equilibrium. This work would provide essential guidance for industrial production.